Evaluation of the Seismic Behavior Based on the Performance of Special Steel Moment Frames by Modified Energy Method and Force Design Method - Ramin Bagherzadeh; Abolfazl Riahi Nouri; Mohammad Sajjad Massoudi; Mohammad Ghazi; Farzan Haddad Shargh (Advances in Civil Engineering)
Although conventional methods in seismic design consider such parameters as force, displacement, and ductility, the behavior of a significant number of structures that have been designed and experienced earthquakes shows that the existing criteria are insufficient and more comprehensive ones should be used. In this regard, the energy-based design method may be considered one of the suitable solutions. This method is based on creating a balance between the input and output energy of structures. It is possible to have a more appropriate estimate of the energy input as well as dissipated energy by the structure and use it in the design of the structure. In the modified energy method that has been used in this study, control of items such as the creation of a soft story, establishment of the Strong-Column Weak-Beam concept, the uniform distribution of loads in the members, the nonconcentration of force and local damage, and simultaneous drift control of the structure with the optimal distribution of plastic hinges have been considered. Also, modifications have been made to the energy balance equation. In this paper, 8-, 16-, and 24-story frames with lateral force resisting system of special steel moment frame have been modified by energy method and compared by the design force method of AISC code. Performance level criteria of the ASCE41-17 code have been applied in the design, and the P−Δ effects have also been considered in the nonlinear analysis. The results show that, for the frame which is designed by the energy method, the plastic hinges are created in the upper stories and beams; however, in the frame designed by the LRFD method, several plastic hinges are formed in the columns of the upper stories, and a local mechanism is created. Also, in 8- and 16-story structures, the weight of the structure which is designed by the energy method is less than that obtained by the LRFD method. The results also showed that, in contrast to the energy method, the relationships presented in the codes regarding the Strong-Column Weak-Beam rule cannot prevent local and undesirable mechanisms in severe earthquakes.